Apa yang Menjadikan Remaja Indonesia Bangga Terhadap Bangsanya? - Nurva Dillatul Vatin; Sartana Sartana (Jurnal Ilmu Perilaku, 2023)
A person's pride in his nation is the main pillar to support the existence and sustainability of the country. Young Indonesians growing up in the era of digital democracy tend to develop a distinctive national identity and source of national pride compared to previous generations. Unfortunately, various things which become a source of pride for Indonesian adolescents towards their nation are rarely explored. This study aimed to identify various sources of national pride for adolescents in Indonesia. Around 385 respondents (aged 18 – 21 years), consisting of 313 females and 72 males involved in the study. The data in this study were collected using an open questionnaire containing one question, "What makes you feel proud as an Indonesian citizen?". The questionnaire was distributed on various social media platforms. Data were analyzed using thematic analysis techniques. The results show that Indonesian adolescents are proud of their nation because of the diverse cultures, ethnicities, languages, religions, and cuisines in Indonesia, as well as the rich and beautiful natural resources and the good climate of Indonesia. Furthermore, young Indonesians are also proud of the local people’s quality and characters and the history and struggle of heroes. Various achievements of the Indonesian people have also become a source of pride for Indonesian youths. The findings indicate that the source of Indonesian adolescents' national pride focuses more on the given things than something that the Indonesian people achieve. Keywords: Adolescents, National Pride, National Identity, Diversity, Indonesian People